2019
DOI: 10.1016/j.rmed.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of idiopathic pulmonary fibrosis by virtual means using “IPFdatabase”- a new software

Abstract: Background: The diagnostic algorithm for idiopathic pulmonary fibrosis (IPF) guidelines has some shortcomings. The aim of the present study was to develop a novel software, "IPFdatabase", that could readily apply the diagnostic criteria per IPF guidelines and make a 'virtual' diagnosis of IPF. Methods: Software was developed as a step-by-step compilation of necessary information according to guidelines to enable a diagnosis of IPF. Software accuracy was validated primarily by comparing software diagnoses to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(23 reference statements)
1
5
0
1
Order By: Relevance
“…However, interobserver agreement in our study is comparable to that of previous study (kappa value 0.66-0.69) [29]. A recent study of 98 patients with ILD showed that the new software, IPFdatabase, can improve interobserver agreement among radiologists (kappa value of 0.18 to 0.64) [30]. Further studies on enhancing the interobserver agreement are warranted.…”
Section: Discussionsupporting
confidence: 85%
“…However, interobserver agreement in our study is comparable to that of previous study (kappa value 0.66-0.69) [29]. A recent study of 98 patients with ILD showed that the new software, IPFdatabase, can improve interobserver agreement among radiologists (kappa value of 0.18 to 0.64) [30]. Further studies on enhancing the interobserver agreement are warranted.…”
Section: Discussionsupporting
confidence: 85%
“…The physical examination identified bilateral basal crackles, lung function tests revealed normal lung volumes and reduced DLCO (40%). HRCT with spiral technique [5,6] demonstrated a definite UIP-pattern associated with the presence of parenchymal consolidations, lymphnodes enlargement and upper lobe emphysema. Cellular analysis of bronchoalveolar lavage (BAL) revealed: macrophages 68%, eosinophils 14%, neutrophils 9% and 9% lymphocytes with a CD4+/ CD8+ ratio 2.93.…”
Section: Dear Editormentioning
confidence: 97%
“…He has worked as a bricklayer, in an oil refinery and finally as truck driver. In 2014 due to chest pain the patient performed high resolution CT (HRCT) with spiral technique [5,6] showing emphysema, fine mantellar and peripheral reticulation, widespread nodules predominantly in the upper lobes and concomitant lymphoadenopathies indicative of sarcoidosis. The patient stayed stable since 2017 when, due to clinical deterioration with dyspnea and dry cough, he performed pulmonary function tests (PFT) revealing mild restrictive deficit and DLCO 52%; the 6 minute walking test and autoantibodies were negative.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations